Fabrication, Characterization and In Vitro Biocompatibility of Electrospun Hydroxyethyl Cellulose/poly (vinyl) Alcohol Nanofibrous Composite Biomaterial for Bone Tissue Engineering - Chahal, Sugandha; Jahir Hussain, Fathima Shahitha; Kumar, Anuj; Mohammad Syaiful Bahari, Abdull Rasad; M. M., Yusoff (Elsevier, 2016)
Development ofnovel scaffold materials that mimic the extracellular matrix, architecturally and func- tionally, is becoming highly important to meet the demands of the advances in bone tissue engineering. This paper reports, the fabrication of natural polymer cellulose derived hydroxyethyl cellulose(HEC) based nanostructured scaffolds with uniform fiber morphology through electrospinning. Poly(vinyl alcohol) (PVA) was used as anionic solvent for supporting the electrospinning of HEC. Scanning electron microscopy and ImageJ analysis revealed the formation of non-woven nanofibers with well-defined porous architecture. The interactions between HECandPVA in the electrospun nanofibers were studied by differential scanning calorimetry, X-raydiffraction, dynamic mechanical analysis thermo-gravimetric analysis; Fourier transform-infrared spectroscopy,X-ray photoelectronspectroscopy and tensiletest. The mechanical properties of scaffolds were significantly altered with different ratios of HEC/PVA. Further, the biocompatibility of HEC/PVAscaffolds was evaluated using human osteosarcomacells. TheSEM images revealed favorable cellsattachment and spreading on the nanofibrous scaffolds and MTS assay showed increased cell proliferation afterdifferent time periods. Thus, these results indicate that HEC based nanofibrous scaffolds will be a promising candidate for bone tissue engineering.